Perceived effectiveness of graphic health warnings as a deterrent for smoking initiation among adolescents in selected schools in southwest Nigeria (2016)
Background: There has been a sustained increment in young people initiating smoking in low middle income countries like Nigeria. Health warnings on cigarette packages are a prominent source of health information and an effective means of communicating specific disease risks to adolescents and young adults alike. This study evaluated the perceived effectiveness of selected graphic warnings on smoking initiation amongst in-school adolescents. Methods: This was a cross-sectional study conducted amongst secondary school students aged 13–17years in Igbo-Ora, Nigeria. A two-stage sampling technique with the school classes as the final sampling unit was used to select the students. An interviewer assisted questionnaire was used to obtain information on students demographic characteristics and their perception of graphic warnings using four images from the pictorial health warning galleries of the World Health Organization showing: ‘cigarette smoking causes cancer of the airways, harms children, causes stroke and causes impotence respectively'. Results: A total of 544 senior secondary students were included in this study with a male female ratio of 0.8:1. Of those interviewed, 40 (7.4 %) indicated that they had ever considered smoking, nine (1.7 %) responded that they had ever smoked and two students indicated that they were current smokers. With all the images, fear was the dominant emotion expressed by the respondents. This was expressed by 307 (56.4), 215 (39.5), 203 (37.3) and 228 (41.9 %) respondents to images 1, 2, 3, and 4 respectively. Furthermore, 76.7, 44.7, 58.5 and 62.1 % of respondents felt Images 1, 2, 3 and 4 respectively will to a large extent prevent people from initiating smoking. There was no association between perceived effectiveness and gender. However, those younger than 15 years rated images on cancer of the airway and impotence as probably effective to a larger extent than did those who were 15 years and older (p = 0.032). Conclusion: Introduction of graphic health warnings, especially with an imagery depicting cancer and impotence may influence non-smokers to remain abstinent. Therefore, this study provides a template for a future policy-relevant study on graphic health warning in Nigeria.